International dictionary of accounting acronyms - Morris, Thomas W. (Glenlake Pub. Co. AMACOM, 1998)
he International Dictionary of Accounting Acronyms is a must for busy executives and professionals who deal with a wide range of accounting and financial issues. Spelling out almost 2,000 acronyms, it takes the mystery out of GAAP, FMT, SEIA and all the other acronyms casually used by accounting professionals and the media. Examples and illustrations are used throughout to clarify the definitions, which are fully cross-referenced for ease of use. An appendix provides sources of additional information.